Penerapan Metode Prototyping Dalam Rancangan Sistem Informasi Absensi Berbasis Website - Fitra Kasma Putra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Employee attendance at the Padang Pariaman Social Service Office uses a fingerprint system, but since April 2020 due to the COVID19 virus, fingerprints cannot be used anymore, this is to reduce the spread of the COVID19 virus. Currently the attendance is implemented in the form of a google form so that it makes data collection and calculation of attendance hours, hours out, until the information does not come in has an impact on the relatively long time in the process of recapitulating attendance from employees, errors in recording data, and making it difficult for the Head of the Administration in the management process. attendance data. Based on these problems the authors designed a website-based information system using the prototyping method using Unified Modeling Language (UML) modeling. The information system created can provide convenience for the administrative section in recapitulating employee attendance data. Then after testing the system using the blackbox method, it was found that all existing features could function as expected.